The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13054-020-03455-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the epidemiology, management, and outcome from acute respiratory distress syndrome in European intensive care units: a comparison of two large cohorts

Abstract: Background Mortality rates for patients with ARDS remain high. We assessed temporal changes in the epidemiology and management of ARDS patients requiring invasive mechanical ventilation in European ICUs. We also investigated the association between ventilatory settings and outcome in these patients. Methods This was a post hoc analysis of two cohorts of adult ICU patients admitted between May 1–15, 2002 (SOAP study, n = 3147), and May 8–18, 2012 (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Driving pressure may also be used to set PEEP since the best compromise between overinflation and recruitment is determined at the lowest Δ P [ 17 ]. A study analyzing two randomized ARDS trials found that a decrease in Δ P was associated with lower mortality compared to increased Pa O2 /F i O2 [ 18 ]. Several concerns exist regarding PEEP titration according to Δ P including (1) depending on the V T used, the lowest Δ P may be achieved at different PEEP levels, (2) at higher C RS , compared to lower C RS , higher PEEP levels may achieve a lower Δ P , (3) the decrease in Δ P with PEEP may be associated with greater intratidal recruitment, (4) changes in chest wall compliance may affect the Δ P measurement, and (5) the presence of airway closure may confound the relationship between Δ P and PEEP.…”
Section: Introductionmentioning
confidence: 99%
“…Driving pressure may also be used to set PEEP since the best compromise between overinflation and recruitment is determined at the lowest Δ P [ 17 ]. A study analyzing two randomized ARDS trials found that a decrease in Δ P was associated with lower mortality compared to increased Pa O2 /F i O2 [ 18 ]. Several concerns exist regarding PEEP titration according to Δ P including (1) depending on the V T used, the lowest Δ P may be achieved at different PEEP levels, (2) at higher C RS , compared to lower C RS , higher PEEP levels may achieve a lower Δ P , (3) the decrease in Δ P with PEEP may be associated with greater intratidal recruitment, (4) changes in chest wall compliance may affect the Δ P measurement, and (5) the presence of airway closure may confound the relationship between Δ P and PEEP.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of arterial (PaO2) to inspired (FiO2) partial pressure of oxygen (P/F ratio), is currently utilized to assess the severity of respiratory failure in patients with ARDS [5] and correlates to mortality rate [6][7][8]. P/F ratio has been recently proposed as a prognostic marker in Covid-19 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[38]Other studies have also stated that the PaO2/FiO2 ratio is correlated with mortality, so the PaO2/FiO2 ratio is proposed as a prognostic marker in Covid-19. [4,6] In COVID-19, inflammation and edema in the alveoli are the main causes of hypoxemia in the early stages of the disease, so the P/F ratio is quite related to the severity of decreased diffusion which is characterized by hypoxemia and a decrease in the PaO2/FiO2 ratio. In the development of COVID-19 disease (consolidation phase), intrapulmonary shunt occurs and causes early arterial hypoxaemia which is mainly caused by ventilation/perfusion imbalance and persistent pulmonary blood flow to unventilated alveoli, and there can be a relative failure of pulmonary vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3]The ratio of partial pressure of oxygen (PaO2) to a fraction of inspired oxygen (FiO2) (P/F ratio), is currently used to assess the severity of respiratory failure in patients with ARDS and correlates with mortality. [2,4,5] The P/F ratio was recently proposed as a prognostic marker in COVID-19. [6] In one study from China with twenty cases of COVID-19, it was found that individuals with severe disease often presented with elevated serum ferritin levels, with statistically significant differences between the severe and mild categories.…”
Section: Introductionmentioning
confidence: 99%